The Discourse on Humour in the Romanian Press between 1948-1965 - Eugen Ignat (Slovo, 2018)
To download a copy of this article, click here. This paper analyses the Romanian official discourse on humour, reflected in the press, between 1948-1965. My analysis distinguishes between three different phases, each proposing a distinct type of humour: the period between 1948-1853, emphasizing satirical comedy as a way of criticizing negative phenomena in society; the transitional period, between 1953-1955 in which the official discourse seems to abandon the stress upon satirical comedy and moves towards one which emphasizes the need to create strong positive characters; and the period between 1956-1965, whose discourse on humour blends together optimistic comedy, centred around positive characters characteristic for the new society, with a benevolent kind of satire.